Regulation of nuclear-factor kappa B signaling pathway by jumonji-domain containing protein 8 / Yeo Kok Siong - Yeo, Kok Siong (2018)
Tumor Necrosis Factor (TNF)-induced signaling mediates pleiotropic biological consequences including inflammation, immunity, cell proliferation and apoptosis. Misregulation of TNF signaling has been attributed as one of the leading causes of chronic inflammatory diseases and cancer. Jumonji domain-containing protein 8 (JMJD8) belongs to the JmjC family. However, only part of the family members has been described as hydroxylase enzymes that function as histone demethylases. Here, JMJD8 was demonstrated to regulate TNF-induced NF-κB signaling positively. Silencing the expression of JMJD8 using RNA interference (RNAi) significantly suppressed the TNF-induced expression of several NF-κB-dependent genes. Moreover, knockdown of JMJD8 expression reduced RIP ubiquitination, IKK kinase activity, delays IκBα degradation and subsequently blocks nuclear translocation of p65. JMJD8 deficiency also enhances TNF-induced apoptosis. Furthermore, bioinformatics analysis and immunofluorescence microscopy were employed to examine the physiological properties of JMJD8. Immunofluorescence microscopy and immunoprecipitation demonstrate that JMJD8 localizes to endoplasmic reticulum (ER) and forms dimers or oligomers in vivo, respectively. Protease protection assay further shows that JMJD8 localized specifically to the ER lumen. In addition, potential JMJD8-interacting proteins that are known to regulate protein complex assembly and protein folding are identified. Taken together, these findings indicate that JMJD8 functions as a positive regulator of TNF-induced NF-κB signaling and JMJD8 represents the first JmjC domain-containing protein found in the lumen of endoplasmic reticulum.